Strategic agility and sustainable competitive advantage of licensed television stations in Kenya: The moderating role of disruptive innovation - Karoney, Farida; Awino, Zachary Bolo; Aosa, Evans; Wainaina, Gituro (International Journal of Economics, Business and Management Studies, 2024)
This study examined the effect of disruptive innovation on the association between strategic agility and sustainable competitive advantage of licensed television stations in Kenya. A comprehensive scrutiny of literature revealed that the effect of disruptive innovation on the nexus between strategic agility and sustainable competitive advantage had not been been empirically tested within the context of licensed television stations in Kenya. The study was anchored on the positivist philosophy and adopted a cross-sectional descriptive research design. 210 television stations that were in operation at the time of the study were surveyed. Research hypotheses were tested using structural equation modelling (SEM), and the findings confirmed that disruptive innovation moderated the relationship between strategic agility and sustainable competitive advantage of licensed television stations in Kenya. While strategic agility had a significant and direct positive influence on sustainable competitive advantage, disruptive innovation enhanced that relationship. The results of this study contribute to literature on strategic agility and some of the contingency conditions necessary for sustainable competitive advantage. The findings have also enhanced the understanding of the competitive forces at play within the television sub sector of the media industry in Kenya. It is recommended that licensed television stations in Kenya pay keen attention to disruptive technologies and strategies such as entry into new markets, acquisition/partnerships with digital start-ups, focusing on underserved or overshot market segments, and experimentation with new business models.